2020
DOI: 10.31254/sportmed.4205
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Coronavirus Disease 2019 (COVID-19) on Physical Activity and Mental Health of Students

Abstract: Background: The novel coronavirus disease 2019 (COVID-19) seems to be having a significant impact on physical activity behaviors globally. The pandemic has forced many of us around the world to remain reception and self-isolate for a period of your time. Aims and Objectives: The aim of this paper was to find out how much the measures due to the COVID-19 pandemic affected the daily lives and how the measures affect the physical activity and mental health of students after 81 days. Materials and methods: A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The authors note that further significant reductions in children's physical activity due to epidemic restrictions are alarming and should be regulated by government agencies and school administrations. Atiković et al [23] note a decrease in the time that schoolchildren began to devote to various types of physical activity during anti-epidemiological measures. However, most studies have shown a decrease in physical activity in different regions.…”
Section: Discussionmentioning
confidence: 99%
“…The authors note that further significant reductions in children's physical activity due to epidemic restrictions are alarming and should be regulated by government agencies and school administrations. Atiković et al [23] note a decrease in the time that schoolchildren began to devote to various types of physical activity during anti-epidemiological measures. However, most studies have shown a decrease in physical activity in different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Para além disso, o período pandémico pode ter reforçado a marginalização da EF, porque foi reduzida ao papel de mecanismo não farmacológico de saúde pública (ATIKOVIĆ et al, 2020;CHEE;HO, 2020;SILVA-FILHO et al, 2020) e a sua orientação educativa diminuída (CRUICKSHANK et al, 2021).…”
Section: Aprendizagemunclassified